Bimbingan Keagamaan Dalam Menangani Problema Bullying Di Kalangan Siswa - Surahman, Muhammad Haziq; Muttaqin, Zaenal; Miharja, Sugandi (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
The purpose of this research is to find out the material of religious guidance, religious guidance methods and stages of religious guidance in dealing with bullying problems among students. The research used a qualitative descriptive approach method. Based on the results of the research, the implementation of religious guidance is carried out by the counselor by providing material on creed, morals and material for reading and memorizing Quranic verses. The counselor uses the lecture method through a behavioral approach, which emphasizes the cognitive dimension of the individual to take clear steps in changing the behavior of the counselee so that bullying does not occur again. Religious guidance is carried out in six meetings. The implementation of religious guidance in an effort to overcome bullying behavior is carried out in groups, namely face-to-face directly between the counselor and the counselee.